Quinhentist doctrines: assumptions and alomorphies between luteranism and anglicanism - Mulza, Giovana Eloá Mantovani (Laboratório Editorial Faculdade de Ciências e Letras, 2017)
The sixteenth-century conjuncture entails an interim of explicit institutional allomorphs, when it accommodates the ascending strengthening of the European state archetype and Protestant reformism. Concomitant with such a contextual framework, it is argued that religiosity assumes assiduity, through a prominence of the metaphysician remains explicit. In addition, the anticlericalism sixteenth century corroborated notoriety, intent that fundamentally the reformist framework. Disparate from doctrinal homogenizations, competing with the historiographer of the ideology of print and profession distinction of Lutheran and Anglican ideologies, as they raise notorious ideological divergences. Therefore, it will be sought to ascertain intrinsic disparities to Lutheranism and Anglicanism, paying attention to assiduity and doctrinal allomorphisms.